Pengaruh Pergantian Auditor dan Kualitas Audit terhadap Opini Audit Going Concern: Studi Empiris Perusahaan Manufaktur di Bursa Efek Indonesia - Djunaidi, Arlen; Soepriyanto, Gatot (Bina Nusantara University, 2013)
This study aims to analyze the effect of auditor switching and audit quality on going concern audit opinion in listed manufacturing companies of the Indonesia Stock Exchange (BEI) in the year 2006 to 2008. Auditor switching was marked by a change to the Public Accountant firms (KAP) who perform the audits or companies used the services of an auditor different than before. Audit quality is proxied by the scale of the BigFour auditors or non-Big Four. Going-concern audit opinion is the explanation given by the auditor if there is any doubt regarding the ability of the company to survive in the future. This study used 70 samples out of 452 populations, using purposive sampling technique in which the main criterion is the sample company received going-concern audit opinion in the year preceding the auditor switched. Results of the study showed that the change of auditors and audit quality is not a factor in determining going concern audit opinion of the company.